Optimal Bandwidth Allocation and Software-Defined Network Aggregation for Heterogeneous Mobile Network - Khaidem Bikramjit Meitei, Thounaojam Rupachandra Singh, Khaidem Panthoi Meetei, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Software Defined Networking (SDN) defines a promising networking architecture combining network programmability and central management. The optimal bandwidth allocation is not attained in the existing system which results in overall network performance degradation. The Adaptive Genetic Algorithm (AGA) is used for attaining the optimal bandwidth allocation so as to improve the overall network performance. A software-defined network aggregation is used in this system for traffic offloading in LTE-WiFi networks. The SDN and Multipath Transmission Control Protocol (MPTCP) can generate TCP subflows across multiple network connection. A centralized controller id used for connecting SDN directly to the subflows and for aligning the rate of subflows in every radio access network for enhancing integrity and load balancing of many-RAT bandwidth aggregation(MRBA). The controller can receive the status of the network and promote network management. The Quality of Experience (QoE) estimation method is used in this system for enhancing QoE of the multimedia device users. The newly designed AGA-MRBA-QoE architecture can give high performance with regard to lower delay, higher bandwidth, higher packet delivery ratio (PDR), higher throughput and lower energy consumption.